Pengaruh Faktor Psikologis terhadap Minat Penggunaan Layanan Keuangan Syariah - Rozi, Gaoz Rozi Fahraini; Selmiana Safitri; Alan Budi Kusuma (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
This research was conducted with the aim of determining the psychological factors that influence people's interest in using sharia financial services. The sampling technique used was a purposive sampling technique with the community population in Alas and Buer Districts calculated using the convenience formula. This research uses a quantitative research method with primary data in the form of a questionnaire. Hypothesis testing uses simple linear regression analysis techniques. So the results obtained in the research show that sharia economic literacy has a positive and significant effect on people's interest in sharia financial services with a significant value of 0.000 < 0.005 with the regression equation, namely Y = 1.118 + 0.227 X.